ENERGY METABOLISM AND CORN RATIONS COMMERCIAL BROILER CHICKENS ON BROILER REJECTED - Wahyudi, Febi Tri; Sudrajat, Deden; Malik, Burhanudin (Jurnal Peternakan Nusantara, 2017)
One of the information needed by farmers is information about nutrition ration poultry in accordance with the Indonesian National Standard (SNI). This study aims to determine the value of energy metabolism in commercial chicken rations. Determination of energy metabolism was conducted by Farrel in which chickens were fed like a chicken eating chicken feed itself and previously fasted for 24 hours and still be drinking. The ration of treatment used is feed corn, feed rations BR1 and BR2. Chickens were given time for 2 hours to eat the feed later in the fasting. After fasting rationing and the chicken will issue feces, to prevent the evaporation of nitrogen in the feces spraying by the use of H2SO4 concentration 0,01%. Chicken feces then dried and analyzed by the laboratory using a bomb calorimeter. The data in the analysis of variance (ANOVA) and Duncan test. Corn research results show that the energy metabolism in the feed ration obtained BR1 3.048 kcal/kg and BR2 3.237 kcal/kg. The result can be concluded that the value is in compliance with EM EM minimum value required in SNI minimum of 2.900 kcal / kg with a value of EM listed on the label.Keywords:Â  Energy Metabolism, Commercial feed, Corn